Detecting abnormal patterns in call graphs based on the aggregation of relevant vertex measures - Alves, Ronnie Cley Oliveira (2012)
Graphs are a very important abstraction to model complex structures and respective interactions, with a broad range of applica- tions including web analysis, telecommunications, chemical informatics and bioinformatics. In this work we are interested in the application of graph mining to identify abnormal behavior patterns from telecom Call Detail Records (CDRs). Such behaviors could also be used to model essential business tasks in telecom, for example churning, fraud, or mar- keting strategies, where the number of customers is typically quite large. Therefore, it is important to rank the most interesting patterns for fur- ther analysis. We propose a vertex relevant ranking score as a unified measure for focusing the search of abnormal patterns in weighted call graphs based on CDRs. Classical graph-vertex measures usually expose a quantitative perspective of vertices in telecom call graphs. We aggre- gate wellknown vertex measures for handling attribute-based information usually provided by CDRs. Experimental evaluation carried out with real data streams, from a local mobile telecom company, showed us the fea- sibility of the proposed strategy.